Analysis of Situational Leadership Model in Maintaining Tradition of Salafiah Education and Science At The Sabilul Hasanah Islamic Boarding School Banyuasin South Sumatra - Adi Sudrajat; Kiemas Badaruddin; Mgs. Nazaruddin (Postgraduate Program Magister Pendidikan Agama Islam, 2021)
This study discusses situational leadership in maintaining the tradition of salafiah education and scholarship at the Sabilul Hasanah Islamic Boarding School, Kab. Banyuasin. The background study is based on the Islamic boarding schools can respond to every change and adapt to the demands of the times but do not eliminate their characteristics as a salaf cottage in which there is a tradition of salafiyah education and scholarship. This study aims to analyze how the situational model of a Kiyai in Islamic boarding schools can combine the Khalafi education system with the salaf while responding to various educational challenges but maintaining the salafiah tradition. This study uses descriptive qualitative methods using a sociological approach and phenomenological research design. Data collection techniques using observation, interviews, documentation, and triangulation. The data that has been collected is analyzed descriptively qualitatively. The study results indicate that the Sabilul Hasanah Islamic boarding school is ready to face the changes and developments of the times by remaining accommodating to these changes. It can be understood that the salaf or traditional does not reject modernity at all. It is just that they do not just accept modernity. Positive changes are resulting from the development of the times and technology. This tradition aims inside to maintain the historical values of Islamic education, spiritual values, attitude, and morals and uphold the attitude of simplicity, tawaddu' and ta'zaim, but also exemplifies local cultural values Public Muslims with the concept of Almuhafadhotu 'ala qodimissholeh (always maintain and maintain good traditions). As for the supporting factors, the religious atmosphere of the area, the curriculum of Islamic boarding schools, qualified teaching staff in yellow books, the cottage curriculum, while the inhibiting factors for learning are so dense, the curriculum is considered old-fashioned learning methods.